SAT0222 Total body and regional bone mineral and soft-tissue composition in hiv disease. (1st June 2001) - Bernard, J; Bonnet, E; Acquilina, C; Hervé, R; Massip, P; Mazières, B
Abstract : Background: Osteopenia and adipose tissue maldistribution are two complications of highly active anti-retroviral therapy (HAART: 1 protease inhibitor + 2 nucleoside reverse transcriptase inhibitors). Dual energy x-rays absorptiometry (DEXA) is a reliable tool to assess total body and regional bone mineral and soft-tissue composition. Objectives: (1) To compare the results of DEXA in HIV-infected patients treated or not with HAART, with or without clinical lipodystrophy and (2) to evaluate DEXA as a tool for early diagnosis of body fat redistribution. Methods: A cross-sectional analysis was performed on 220 men. All subjects gave written informed consent. Controls (C): 106 healthy uninfected volunteers without medical or surgical history, nor immobilisation and therapies which may modify bone mineral density, mean age 38 years. One hundred and fourteen HIV-infected patients at steady-state, without opportunist disease, nor prophylactic drugs? use were divided in 3 groups: (i) 20 naive HIV-patients (N: mean age 38 years, disease duration 43 mths, viral load 3.7 log, CD4 + 417/mm 3 ), (ii) 32 HIV-treated patients with no clinical lipodystrophy (n-CLD: mean age 35, disease duration 72 mths, HAART duration 15 mths, viral load 2.3 log, CD4 + 524/mm 3 ), and (iii) 62 HIV-treated patients with clinical lipodystrophy (CLD: mean age 42, disease duration 94 mths, HAART duration 26 mths, viral load 1.8 log, CD4 + 483/mm 3 ). Total body and regional soft-tissue composition were measured with DEXA (DPX-L, Lunar Corp. Acquisition and analysis software 4.6). The following parameters were studied: Fat Mass% (FM, %), Lean Mass (LM, kg), Bone Mineral Content (BMC, mg), and Fat Mass Index (FMI: trunk fat mass/legs fat mass). Statistics. Mean ± SD, ANOVA, Scheffe's F procedure for post-hoc comparison. Results: Lean Mass was the same in the 4 groups. Despite 43 months of disease duration, Naive and Controls had the same fat mass, BMC and FMI. The two treated HIV-infected groups had lower Fat Mass and upper Fat Mass Index than Controls. Loss in Fat Mass at the expense of the legs was proportional to duration of HAART. The great variability of the FMI (SD) in these two groups suggested a poor clinical sensitivity to change. Decrease of BMC seemed treatment-dependent. Lipodystrophy appeared also age-related. Conclusion: DEXA allows an early diagnosis of fat maldistribution. We propose to perform this exam to all HIV-infected patients once a year before treatment and every 6 months in patients under treatment.